2014
DOI: 10.5851/kosfa.2014.34.5.674
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Meat Qualities of Loin and Top Round Beef from Holstein Calves with Different Slaughtering Ages

Abstract: The objective of this study was to investigate the physico-chemical and sensory properties of loin (m. longissimus dorsi) and top round (m. semimembranosus) beef from 3-, 6-, 9-, and 12 mon-old Holstein calves. For both loin and top round muscles, the moisture contents were decreased, whereas the protein and fat contents were increased, as the slaughtering age increased. In terms of meat color, for both muscle types, CIE L* values were decreased, whereas CIE a* values and myoglobin content increased as the sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
7
10
0
Order By: Relevance
“…This is in agreement with previous reports [7, 16] has indicated WHC in Holstein loin muscles increased with older age. On the other hands, Cooking loss and the shear force values of both muscles for the 5 month group was significantly higher than those for the 8 month group.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This is in agreement with previous reports [7, 16] has indicated WHC in Holstein loin muscles increased with older age. On the other hands, Cooking loss and the shear force values of both muscles for the 5 month group was significantly higher than those for the 8 month group.…”
Section: Resultssupporting
confidence: 94%
“…Fat and protein contents for the 8 month group were higher than those for the 5 month groups. This is in similar to the ones found by Cho et al [7] who indicated the protein and fat contents were increased with increasing month of age. Similarly, previous studies [12, 13] also found that protein content in beef loin muscles increased with advancing age.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations